Analisis Manajemen Kinerja Dalam Mendukung Sistem Akuntabilitas Kinerja Instansi Pemerintah Di Kabupaten Kepulauan Yapen Propinsi Papua - Dolfinus Ayomi; Ermaya Suradinata; Ismail Nurdin (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2023)
This research is entitled Analysis of Performance management in supporting the Government Agency Performance Accountability System in the Yapen Islands Regency of Papua Province which raises the issue of the implementation of local government performance management which is considered to have not been running as expected. The Government Agency Performance Accountability System is an effort to realize a government that is accountable, professional, has integrity, is clean and free of KKN (Corruption, Collusion and Nepotism), and is able to provide excellent and equitable services to the community. The reality that occurs in the administration of government in the island district that Performance Management has not been implemented properly so that it has a negative impact on the value of the Government Agency Performance Accountability System based on the assessment of the Ministry of Administrative Reform and Bureaucratic Reform. The research method used is a qualitative research method to formulate the ideal conditions for implementing performance management in the regional government of the Yapen Islands Regency. Furthermore, to analyze Local Government Performance Management in supporting the Performance Accountability System in the Yapen Islands Regency, researchers used ASOCA analysis, which stands for (Ability, Strength, Opportunities, Culture and Agility). According to Suradinata (2014: 18) says that the ASOCA analysis adds elements of culture and agility as important elements in finding problem-solving strategies, decision making, and can be developed in following changes, times, and needs. Based on the data and analysis previously described, it can be concluded that Performance Management has been implemented in the Yapen Islands Regency, especially in measuring local government performance which can be seen from regional level planning documents or RPJMD and Regional Apparatus level documents, namely Renstra, but understanding of SAKIP is still not optimal so that it has implications for its implementation. HR management needs to be reconstructed so that it is in accordance with the targeted tasks and functions. The strategy that can be carried out by the Regional Government of the Yapen Islands Regency is to optimize the capacity of human resources related to understanding performance management and SAKIP by conducting massive and comprehensive technical guidance to each regional apparatus.